Implementasi Kurikulum Merdeka dan Penilaian Karakter dalam Pembelajaran PJOK - Rizki Utami Dewi; Cucu Hidayat; Nanang Kusnadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The purpose of this study is to analyze the role of physical education in the development of character, motivation, and student participation through a literature review of relevant studies. The research method used is a narrative literature review with a staged selection process of articles obtained from the Scopus, Taylor & Francis, SAGE, and Google Scholar databases indexed in SINTA. The results of the study indicate that physical education plays an important role in developing character values such as discipline, responsibility, cooperation, and sportsmanship through direct and interactive learning experiences. In addition, psychological factors such as autonomous motivation and body image perception influence the level of student participation in physical education learning. The implementation of inclusive pedagogical approaches, the incorporation of student voice, and the connection of learning activities with real-life contexts are also shown to enhance student engagement and learning experiences. In conclusion, physical education has a strategic role in supporting the development of character, motivation, and student participation; therefore, strengthening teacher competencies, providing policy support, and promoting innovative learning approaches are necessary to optimize the implementation of physical education. Keywords: Body Image, Character, Inclusive Pedagogy, Physical Education, Student Motivation